Toll-Like Receptor 6 Plays an Important Role in Host Innate Resistance to Brucella abortus Infection in Mice - Almeida, Leonardo A. de (2013)
Brucella abortus is recognized by several Toll-like receptor (TLR)-associated pathways triggering proinflammatory responses that affect both the nature and intensity of the immune response. Previously, we demonstrated that B. abortus-mediated dendritic cell (DC) maturation and control of infection are dependent on the adaptor molecule MyD88. However, the involvement of all TLRs in response to B. abortus infection is not completely understood. Therefore, we decided to evaluate the requirement for TLR6 in host resistance to B. abortus. Here, we demonstrated that TLR6 is an important component for triggering an innate immune response against B. abortus. An in vitro luciferase assay indicated that TLR6 cooperates with TLR2 to sense Brucella and further activates NF-κB signaling. However, in vivo analysis showed that TLR6, not TLR2, is required for the efficient control of B. abortus infection. Additionally, B. abortus-infected dendritic cells require TLR6 to induce tumor necrosis factor alpha (TNF-α) and interleukin-12 (IL-12). Furthermore, our findings demonstrated that the mitogen-activated protein kinase (MAPK) signaling pathway is impaired in TLR2, TLR6, and TLR2/6 knockout (KO) DCs when infected with B. abortus, which may account for the lower proinflammatory cytokine production observed in TLR6 KO mouse dendritic cells. In summary, the results presented here indicate that TLR6 is required to trigger innate immune responses against B. abortus in vivo and is required for the full activation of DCs to induce robust proinflammatory cytokine production.